Cyclic behavior of non-seismically detailed full-scale exterior beam-column subassemblies with setback in columns. (January 2022) - Zhao, X.Y.; Zhang, H.Y.; Wu, B.; Jin, H.M.; Leung, K.T.; Lau, L.S.; Lee, K.H.
Abstract: Discontinuity in cross-section depth may exist in RC columns. If present in a non-seismically detailed frame, such a discontinuity (termed herein setback in columns, SBC ) may trigger unexpected seismic damage. However, this typology of irregularity within connections has long been overlooked. This paper offers initial experimental evidence showing how vulnerable these irregular, non-conforming RC connections would be under earthquake-like loading. Four full-scale exterior beam-column subassemblies with SBC were constructed and cyclically tested, including three "as-built" units and a control one improved with seismic detailing. Results indicated that all the units succumbed to joint shear failure, and exhibited distinctly asymmetric responses in different loading directions. Particularly, when subjected to a positive (sagging) beam moment, the "as-built" units displayed a very steep joint cracking pattern and, hence, remarkably lower peak loads as compared to the case where a negative (hogging) beam moment was applied. Possible causes inducing such a salient failure mode are discussed, and a detailed account of the cyclic behaviors of the four units presented. Moreover, based on the concept of wide and narrow joint panels, existing major code provisions and analytical procedures for regular connections were adapted to evaluate the joint shear capacity of the current irregular subassemblies. A practical modeling approach was also developed through ABAQUS user-defined subroutine for capturing the observed global hysteretic responses. Overall, the outcomes of this study highlight the vulnerability of non-seismically detailed exterior connections with SBC, and provide a reference for future related research.